Kemiskinan Multidimensi - Adi, Isbandi Rukminto (Makara Human Behavior Studies in Asia, 2005)
Poverty is one of many problems that always been discussed from generation to generation. Especially, after the monetary and economic crisis where the number of people who live below poverty line was increased rapidly. This article will discuss the Poverty problems from the multi-dimensional standpoint which has been adopted by the social development approach. This approach view problem from the micro, mezzo and macro dimensions. After discussing several roots of poverty, this article will suggests an alternative strategy which can be undertaken in order to reduce the number of Indonesian people who live below the poverty line. This strategy also include the strategy to improve the existing condition by changing the micro, mezzo, and macro dimensions which has been analysed before.